A new record of Cryptocephalus barii Burlini, 1948 (Coleoptera Chrysomelidae) from Mount Grigna Settentrionale (Lombard Pre-Alps), with some ecologica! notes. (Bollettino di zoologia agraria e bachicoltura, 2024)
The rare and localyzed species Cryptocephalus barii Budini, is recorded from Mount Grigna Settentrionale (Lombard Pre-Alps). Some ecological information and the drawing of the spermatheca are also given.
Keywords: Chrysomelidae; Cryptocephalus barii; host plant